Biodiversity and springtime patterns of egg production and development for parasites of the Chisana Caribou herd, Yukon Territory, Canada - Hoar, Bryanne; Oakley, Michelle; Farnell, Rick; Kutz, Susan (Rangifer, 2009)
We investigated the biodiversity and springtime patterns of parasite egg/oocyst and larval production from feces and parasite development in the environment for the Chisana caribou herd in the southwest Yukon Territory, Canada from 29 March to 14 June 2006. Fecal samples from 50 adult cows that were housed in a temporary enclosure within the herd’s natural range at Boundary Lake, Yukon Territory were collected and analyzed during 5 sampling periods. A minimum of 6 parasite genera were recovered: eggs of Trichostrongylidae species (most likely Ostertagia gruehneri and Teladorsagia boreoarcticus), Marshallagia sp., Anoplocephalidae cestodes, and Skrjabinema sp.; oocysts of Eimeria spp.; and dorsal-spined first-stage protostrongylid larvae, including Parelaphostrongylus andersoni. Prevalence of Trichostrongylidae spp. eggs in fresh fecals was at or near 100% throughout the sampling period, however, the median intensity increased significantly from 8 to 34 eggs per gram (epg) at the peak of calving and then decreased to 12 epg 2 weeks post-calving (P = 2.83e-07). Three plots of feces collected from these animals were established outside of the enclosure on 4 May 2006 and monitored every 10 days to investigate patterns of parasite development under natural conditions. The total number of Trichostrongylidae spp. (eggs + larvae) in fecal plots did not change over time, but as the number of larvae increased, egg counts decreased. The presence of other parasite species in the fecal plots remained constant over time. This study is the first to document the parasite diversity for the Chisana caribou herd and to exam¬ine the development and survival of eggs and larvae in feces throughout the spring and early summer. Abstract in Norwegian / Sammendrag: Parasitters artssammensetning og forløp av eggproduksjon og parasittutvikling om våren hos Chisanavillreinen i Yukon, Canada I en periode fra 29. mars til 14. juni 2006 tok vi prøver fra reinmøkk og under¬søkte artsammensetning, egg/oocysteproduksjon og parasittutvikling i et område sørvest i Yukon, Canada, der Chisana caribou’en holder til. Møkkprøver fra 50 voksne simler, holdt i en midlertidig inngjerding i det naturlige beiteområdet ved Bondary Lake, ble samlet og analysert i løpet av fem prøveperioder. Parasitter fra minst seks slekter ble funnet: materialet omfattet egg av Trichostrongylidae-arter (mest sannsynlig Ostertagia gruehneri og Teledorsagia boreoarcti¬cus), Marshallagia-art, Anaplocephalidae-bendelmark og Skrjabinema-art, oocyster av Eimeria-arter, og ryggpiggete førstestadiums Protostrongylidae-larver, bl.a. av Parelaphostrongylus andersoni. I ferske møkkprøver var prosentvis tilstedeværelse av Trichostrongylidae-egg nesten 100 % gjennom prøveperioden, men median intensitet (parasittmengde) økte statistisk signifikant fra 8 til 34 egg per gram under kalvingens mest intense periode og avtok til 12 egg per gram to uker etter kalving. Møkk fra forsøkssimlene ble den 4. mai plassert i tre felt utenfor området der simlene ble holdt inngjerdet, og undersøkt hver tiende dag for å følge parasittutviklingen under naturlige betingelser. Det totale antall av egg + larver Trichostrongylidae i feltene forandret seg ikke; larvemengden økte samtidig som eggmengden avtok. Tilstedeværelsen av andre parasitter i feltene forble også konstant over tid. Vår studie er den første til å dokumentere parasittdiversiteten i Chisanavillreinen og å undersøke utviklingen og overlevelsen av egg og larver gjennom vår og tidlig sommer.